Bond strength of self-adhesive resin cements to a high transparency zirconia crown and dentin - Jeng-Fen Liu; Chun-Chuan Yang; Jun-Liang Luo; Yu-Ching Liu; Min Yan; Shinn-Jyh Ding (Elsevier, 2022)
Background/purpose: The bond strength and durability of highly translucent zirconia ceramics to dentin is still unclear. The purpose of this study was to investigate the effect of various surface treatments on the bond strength of self-adhesive resin cements to high-translucent zirconia crowns and dentin. Materials and methods: A high-transparent zirconia and three self-adhesive resin cements (G-CEM LinkAce (GCL), RelyX U200 (RXU) and TotalCem (TTC)) were used. The zirconia surface was sandblasted with 50 μm alumina particles or coated with an SR Link primer, while a dentin primer (Tetric N-Bond Universal, TBU) was applied to the surface of the dentin. By using three self-adhesive resin cements, zirconia samples were bonded to the dentin surfaces of human teeth. The shear strength of the specimens was measured before and after 10,000-cycle thermocycling or 90-day aging. Results: When using GCL to bond with the untreated dentin and various zirconia surfaces, the shear bond strength of the sandblasted (ZSB) and RS Link primer-coated (ZLK) groups was significantly higher than that of the untreated control group (Zc). However, in the case of TBU-treated dentin, the shear strength of the ZSB + LK + DTBU group was significantly higher than that of the other groups. After thermocycling and aging, the shear strength of the ZSB + LK + DTBU group using GCL and RXU cements decreased slightly, while the TTC showed no impact. Conclusion: The zirconia surface pretreated by sandblasting and bonding agent, which was sequentially bonded with a primer-treated dentin by using resin cements, can provide excellent shear bond strength and anti-aging performance.